Integrative Framework for Strategic and Sustainable CSR of Microfinance Institutions - Kevin Rivera; Aditya Halim Perdana Kusuma Putra (Manunggal Halim Jaya, 2026)
The study comprehensively reviews the literature of corporate social responsibility (CSR) - related activities, CSR assessment, and CSR sustainability within the context of microfinance institutions (MFIs). This research employs a systematic literature review of peer-reviewed journal articles published in the recent decade that were retrieved from major academic databases and analyzed following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines with inclusion criteria focusing on open-access, English-language, and peer-reviewed studies. From an initial pool of 807 articles, 86 met the criteria for detailed review, and 31 were ultimately selected to inform the development of a comprehensive framework. The results reveal that CSR activities in MFIs are strongly influenced by assessment metrics based on OECD-DAC evaluation criteria and sustainability measures grounded in the Global Reporting Initiative (GRI) indicators. The reviewed articles demonstrate both direct and indirect relationships between CSR and sustainability with prevailing variables such as stakeholder trust, organizational commitment, transparency, governance, and social legitimacy. The findings show that CSR contributes significantly to institutional resilience, reputation enhancement, stakeholder engagement, and long-term sustainability outcomes in MFIs, suggesting that strategically aligned CSR-related activities form an integrative framework that enhances both organizational performance and broader social impact.